Probing medulloblastoma initiation at the single-cell level - Okonechnikov, Konstantin; Pfister, Stefan; Kutscher, Lena (Trends in cancer, 2019)
Medulloblastoma is a pediatric brain tumor arising from the developing cerebellum. Despite significant strides in classifying tumor subgroups and identifying underlying genetic mutations, progress in clinical outcomes has been notably slower. About 30% of patients experience relapse after treatment, possibly because of our inability to identify and eliminate the cancer stem cells. Zhang et al. recently investigated these cells in the SHH subgroup of medulloblastoma and identified drugs that may target them.